Multigeneration responses of Daphnia magna to short-chain per- and polyfluorinated substances (PFAS) - Ge Xie; Cornelis A.M. van Gestel; J. Arie Vonk; Michiel H.S. Kraak (Ecotoxicology and Environmental Safety)
Short-chain per- and polyfluorinated substances (PFAS) are ubiquitous in the environment, but their chronic effects on aquatic organisms over multiple generations are often overlooked in environmental risk assessment. In this study, the ecotoxicity of perfluorobutane sulfonic acid (PFBS) and its precursor perfluorobutane sulfonamide (FBSA) to Daphnia magna was assessed under continuous exposure for six consecutive generations, with adult survival, reproduction, and population growth rate as endpoints. Observed effects were also related to internal PFAS concentrations in the daphnids. Compared to the first generation, both PFBS and FBSA showed intensified ecotoxicity over six generations, increasing by 1.8–3.0, and 3.6–6.4 times, respectively. Specifically, the EC50_r, water and LC50, water of PFBS decreased from 886 and > 1470 mg/L in the F0 generation to 470 and 483 mg/L, respectively in the F3 generation, while the EC50_r, water and EC50_repro, water of FBSA decreased from 12.4 and 7.08 mg/L in the F0 generation to 3.37 and 1.10 mg/L, respectively in the F5 generation. PFBS ecotoxicity increased as a result of elevated compound accumulation over generations, indicating a narcotic mode of action, whereas FBSA exerted specific reproductive toxicity, resulting in a more pronounced worsening of adverse effects over time. Compared to PFBS, FBSA was around 100 times more toxic in F0, escalating to over 435 times more toxic in F5, and also showed a higher bioaccumulation potential. These findings highlight that the conventional single-generation ecotoxicity tests underestimate PFAS ecotoxicity during multigeneration exposure, and that the environmental risks of PFAS cannot be reliably assessed by the current limited subset of studied compounds.